Q: How do you expand x(3x plus 2)?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(3x - 1) + 7 = (7x - 2x) + x3x - 1 + 7 = 7x - 2x + x3x + 6 = 6x6 = 3xx = 6/3 = 2

3(x plus 2) expanded --> 3x+6 Check out wolframalpha.com for more explanation (not advertising)

-4.2x - 6y + 3.6

You can expand the first expression in parentheses, then add or subtract like terms.

16 + 20 + 14 = 50 = 12 + 14 +14 + 10

Related questions

(3x - 1) + 7 = (7x - 2x) + x3x - 1 + 7 = 7x - 2x + x3x + 6 = 6x6 = 3xx = 6/3 = 2

The cast of X3X - 1934 includes: Monang Carvajal Rosa Del Rosario Norma del Rosario Mary Walter

3(x plus 2) expanded --> 3x+6 Check out wolframalpha.com for more explanation (not advertising)

You expand x(x+2) which is x2+2x.

No. If you expand (a + b)2 you get a2 + 2ab + b2. This is not equal to a2 + b2

-4.2x - 6y + 3.6

-4.2x - 6y + 3.6

Expand z plus 11 times z plus 11 = (z+11)(z+11) = z2 + 22z + 121.

You can expand the first expression in parentheses, then add or subtract like terms.

-4.2x - 6y + 3.6

It IS expanded.

they got plus sizes=]